Characterization and performance of W-ZSM-5 and loaded Cu/ZsM-5 catalysts - Didi Dwi Anggoro; Nor Aishah Saidina Amin (Jurnal Teknik Kimia Indonesia, 2005)
The metal oxides with sufficiently high dehydrogenation and low olefin oxidation activities reduces the acidity of ZSM-5. As a result, the metal containing ZSM-5 can produce higher hydrocarbons in methane oxidation. Many researchers studied the applicability of HZSM-5 and modify ZSM-5 to methane conversion to liquid hydrocarbons but result of their research still lead to low conversion and selectivity. The modified HZS-5 by loading with Tungsten (W) enhanced its heat resistant performance, and the high reaction temperature (800ºC) did not lead to the loss of W component by sublimation. The loading of HZSM-5 with Tungsten and Cooper (Cu) resulted in an increment in the methane conversion, CO2 and C5+ selectivities. In contrast, CO, C2-3, and H2O selectivities were reduced. The process to convert methane to liquid hydrocarbons (C5+) was dependent on the metal surface area and the acidity of zeolite. The high methane conversion and C5+ selectivity, and low H2O selectivity are obtained by using W/3.0Cu/HZSM-5.  Keywords : Characterization W-ZSM-5, Modified HZSM-5, Tungsten, Copper, Methane  Abstrak  Logam oksida dengan kemampuan dehidrogenasi yang tinggi dan aktifasi oksidasi olefin berkurang dengan sifat keasaman dari ZSM-5. Sebagai hasilnya, ZSM-5 yang mengandung logam dapat memproduksi hidrokarbon rantai panjang dari oksidasi gas metana. Telah banyak para peneliti mempelajari kemampuan HZSM-5 dan ZSM-5 yang telah dimodifikasi untuk mengubah gas metana menjadi hidrokarbon cair tetapi hasil konversi dan selektivitasnya masih rendah. Modifikasi HZSM- 5 dengan penambahan logam Tungsten (W) meningkatkan daya tahan panas dan pada reaksi suhu tinggi (800ºC) tidak menyebabkan hilangnya logam W dikarenakan proses sublimasi. Penambahan logam Tungsten dan Copper (Cu) menyebabkan meningkatnya konversi metana, selektifitas CO2 dan C5+ Sebaliknya, selektifitas CO,C2-3, dan H2O menurun. Proses konversi metana menjadi hidrokarbon cair ditentukan oleh luas permukaan logam dan sifat keasaman dari zeolite.  Penggunaan katalis W/3.0Cu/HZSM-5 menghasilkan konversi metana dan selektifitas C5+ tinggi dan selektifitas H2O rendah.  Kata kunci : Karakterisasi W-ZSM-5, Modifikasi HZSM-5, Tungsten, Copper, Metana